The Minbar of Saladin : Reconstructing a Jewel of Islamic Art - Singer, Lynette (UK; Thames & Hudson, 2008)
This book on the Minbar's reconstruction tells of the quest to fathom the principles of Islamic sacred geometry and to decipher how the Minbar's complex patterns were created. This was followed by a worldwide search for materials and for craftsmen who still possessed the necessary skills$1 (Bskills that had seemed lost in today's world of mass production and modern technology. n extraordinary piece of craftsmanship, the Minbar, or pulpit, had been installed by Saladin in the mosque on his triumphant recapture of Jerusalem from the Crusaders in 1187. Made of 16,000 pieces of intricately carved wood, adorned with ivory and ebony, it was widely acknowledged as a pinnacle of Islamic design and woodcarving. The book also illustrates the work of the Prince of Wales's School of Traditional Arts in London and the College of Traditional Islamic Arts & Architecture in al-Salt, Jordan, where many of the crafts for which Islamic art and architecture are celebrated are being revived. Published to accompany the documentary film Stairway to Heaven, narrated by Kenneth Branagh. Forewords by HRH The Prince of Wales and HRH Prince Ghazi bin Muhammad of Jordan. 200 illustrations, 170 in color.s
English
Keywords: Islamic geometry; Muslim heritage; NA190-1555.5 Architecture- History; Palestine -- Jerusalem